New Vision for Visual Prostheses - Farnum, Alexander; Pelled, Galit (Frontiers in Neuroscience, 2020)
Developments of new strategies to restore vision and improving on current strategies by harnessing new advancements in material and electrical sciences, and biological and genetic-based technologies are of upmost health priorities around the world. Federal and private entities are spending billions of dollars on visual prosthetics technologies. This review that describes the most current and state-of-the-art bioengineering technologies to restore vision. This includes a thorough description of traditional electrode-based visual prosthetics that have improved substantially since early prototypes. Recent advances in molecular and synthetic biology have transformed vision-assisted technologies; For example, optogenetic technologies that introduce light-responsive proteins offer excellent resolution but cortical applications are restricted by fiber implantation and tissue damage. Other stimulation modalities, such as magnetic fields, have been explored to achieve non-invasive neuromodulation. Miniature magnetic coils are currently being developed to activate select groups of neurons. Magnetically-responsive nanoparticles or exogenous proteins can significantly enhance the coupling between external electromagnetic devices and any neurons affiliated with these modifications. The need to minimize cytotoxic effects for nanoparticle-based therapies will likely restrict the number of usable materials. Nevertheless, advances in identifying and utilizing proteins that respond to magnetic fields may lead to non-invasive, cell-specific stimulation and may overcome many of the limitations that currently exist with other methods. Finally, sensory substitution systems also serve as viable visual prostheses by converting visual input to auditory and somatosensory stimuli. This review also discusses major challenges in the field and offers bioengineering strategies to overcome those.